A case of pulmonary carcinoid tumour in a pregnant woman successfully treated with bronchoscopic (electrocautery) therapy. (22nd April 2013) - Binesh, Fariba; Samet, Mohammad; Bovanlu, Taghi Roshan
Abstract : We present an uncommon case of a carcinoid tumour of the bronchus that was diagnosed during pregnancy in a 28-year-old woman. The patient was admitted at the emergency department with massive haemoptysis. Owing to the patient's critical condition, she underwent urgent flexible bronchoscopy. Bleeding was controlled by local injection of 500 mg tranexamic acid and electrocautery. After the bleeding has stopped, multiple specimens were taken. Histological examination confirmed typical carcinoid tumour. Owing to repeated haemoptysis, she was treated with bronchoscopic (electrocautery) therapy, and, after delivery, she underwent pulmonary lobectomy. Only a few similar cases were found in the literature reporting bronchopulmonary carcinoid tumour during pregnancy and we could not find any similar case which was treated by electrocautery.